Five personality dimensions and their influence on information behaviour - Jannica Heinstrom (Information Research: An International Electronic Journal)
This article emphasize the importance of considering psychological mechanisms for a thorough understanding of users of information services. The focal point is the relation between personality and information seeking which is explored through a quantitative analysis of 305 university students' personality traits and information habits. It is shown that information behaviour could be connected to all the personality dimensions tested in the study - neuroticism, extraversion, openness to experience, competitiveness and conscientiousness. Possible explanations for these relations are discussed. It is concluded that inner traits interact with contextual factors in their final impact on information behaviour.